European Consensus Guidelines on the Management of Neonatal Respiratory Distress Syndrome in Preterm Infants-2013 Update - ÖZEK, EREN (KARGER, 2013)
Despite recent advances in the perinatal management of neonatal respiratory distress syndrome (RDS), controversies still exist. We report updated recommendations of a European Panel of expert neonatologists who developed consensus guidelines after critical examination of the most up-to-date evidence in 2007 and 2010. This second update of the guidelines is based upon published evidence up to the end of 2012. Strong evidence exists for the role of antenatal steroids in RDS prevention, but it is still not clear if the benefit of repeated courses on respiratory outcomes outweighs the risk of adverse outcomes in the short and long term. Many practices involved in preterm neonatal stabilization at birth are not evidence based, including oxygen administration and positive pressure lung inflation, and they may at times be harmful. Surfactant replacement therapy is crucial in the management of RDS but the best preparation, optimal dose and timing of administration at different gestations is not completely clear. In addition, use of very early continuous positive airway pressure (CPAP) has altered the indications for prophylactic surfactant administration. Respiratory support in the form of mechanical ventilation may be lifesaving but can cause lung injury, and protocols should be directed at avoiding mechanical ventilation where possible by using non-invasive respiratory support such as CPAP. For babies with RDS to have best outcomes, it is essential that they have optimal supportive care, including maintenance of normal body temperature, proper fluid management, good nutritional support, appropriate management of the ductus arteriosus and support of the circulation to maintain adequate tissue perfusion. Copyright (c) 2013 S. Karger AG, Basel
Keywords: Antenatal steroids; Continuous positive airway pressure; Evidence-based practice; Hyaline membrane disease; Mechanical ventilation; Oxygen supplementation; Patent ductus arteriosus; Preterm infant; Respiratory distress syndrome; Surfactant therapy; Thermoregulation; BIRTH-WEIGHT INFANTS; POSITIVE AIRWAY PRESSURE; LIBERAL HEMOGLOBIN THRESHOLDS; LESS-THAN-30 WEEKS GESTATION; INHALED NITRIC-OXIDE; OXYGEN-SATURATION; RANDOMIZED-TRIAL; ANTENATAL CORTICOSTEROIDS; SURFACTANT REPLACEMENT; CAFFEINE THERAPY